Precise measurement of the neutrino mixing parameter θ23 from muon neutrino disappearance in an off-axis beam. - Abe, K; Adam, J; Aihara, H; Akiri, T; Andreopoulos, C; Aoki, S; Ariga, A; Ariga, T; Assylbekov, S; Autiero, D; Barbi, M; Barker, G; et al. (American Physical Society, 2014)
New data from the T2K neutrino oscillation experiment produce the most precise measurement of the neutrino mixing parameter θ23. Using an off-axis neutrino beam with a peak energy of 0.6 GeV and a data set corresponding to 6.57×10(20) protons on target, T2K has fit the energy-dependent νμ oscillation probability to determine oscillation parameters. The 68% confidence limit on sin(2)(θ23) is 0.514(-0.056)(+0.055) (0.511±0.055), assuming normal (inverted) mass hierarchy. The best-fit mass-squared splitting for normal hierarchy is Δm32(2)=(2.51±0.10)×10(-3)  eV(2)/c(4) (inverted hierarchy: Δm13(2)=(2.48±0.10)×10(-3)  eV(2)/c(4)). Adding a model of multinucleon interactions that affect neutrino energy reconstruction is found to produce only small biases in neutrino oscillation parameter extraction at current levels of statistical uncertainty.